On summer courses abroad (Journal of Parents and Teachers, 2014)
Summer courses abroad are great opportunities for young people to continue their education during the summer. They are also a complete cultural experience. There are two types of summer courses abroad: homestay or boarding school; both options offer many advantages for young people in training. The article gives advice on choosing the most suitable program for the child and for the parents. It also explains what to look out for.
Keywords: travel; education; activities; summer; courses; courses abroad; advice